SAFETY INSIGHTS: APPLICATION OF THE IDEACM HAZARD ASSESSMENT SHEET INSPIRED BY ‘AVATAR: THE WAY OF WATER’ TO REDUCE OCCUPATIONAL ACCIDENTS AMONG SMALL-SCALE FISHERMEN - Dinda Okta Dwiyanti Ridwan Gucci; Muhammad Adi Sukma Nalendra; Azrat Nur Inayat (International Archives of Medical Sciences and Public Health, 2026)
Work accidents among fishermen remain a critical occupational safety challenge in Indonesia, driven by inadequate implementation of health and safety culture in maritime environments. This research applies the IDEACM (Identification, Design, Evaluate, Adaptation and Control of Macroergonomics) hazard assessment sheet, a structured instrument grounded in macroergonomic principles, to systematically evaluate occupational hazards among small-scale fishermen in Batam. The IDEACM framework was inspired by occupational safety practices depicted in the film ’Avatar: The Way of Water,’ analyzed through Roland Barthes’ semiotics and Fogg Behavior Model. Data were collected through field observations, a 20-item questionnaire (n=10), Focus Group Discussions (FGD), and semiotic film analysis, validated via SPSS (Cronbach Alpha = 0.890). IDEACM assessment quantified hazard scores across five macroergonomic elements (Human, Organization, Technology, Environment, Employment), yielding 18 sub-criteria with priority rankings. The top four hazards were: Skill deficiency in Human element (Score: 4.448, Rank 1); Machine hazards in Technology (Score: 1.00, Rank 2); Equipment risks (Score: 0.79, Rank 3); and absence of K3 Policy in Organization (Score: 0.73, Rank 4). Based on IDEACM findings, three hierarchy controls were designed: Engineering Controls (engine noise enclosures, distress siren systems); Administrative Controls (SOPs, K3 policies, structured shift schedules); and Personal Protective Equipment (PPE). Elimination and substitution were found infeasible under current conditions. The IDEACM framework proved effective as a replicable, structured tool for maritime occupational safety assessment.